1989
DOI: 10.1111/j.1432-1033.1989.tb15218.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin‐binding sites at the surface of HT29‐D4 cells

Abstract: The binding of '251-lactoferrin to HT29-D4 cells, a clone of HT29 cells, was studied and compared to the binding of '"1-transferrin to the same cells. The binding of the two iron-transport proteins is saturable and reversiblc suggesting the presence of specific reccptors for each protein. Scatchard analysis suggests the existence of binding sites for lactoferrin with the relatively high equilibrium dissociation constant, K d l of 408 nM. Additionally, the cell is capable of binding large amounts of lactoferrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…If lactoferrin itself acts as a transcriptional factor that binds to the promoter region of the specific gene, it must first be established that lactoferrin can be transported to the nucleus from the outside of the cell. Several researchers have reported on the lactoferrin-specific receptor to which lactoferrin binds, as well as the translocation of the intact lactoferrin into nucleus [Garre et al, 1992;Hu et al, 1990;Roiron et al, 1989;Mazurier et al, 1989]. Once it can be translocated into the nucleus, it binds easily to the DNA [Ravazzollo et al, 1988].…”
Section: Discussionmentioning
confidence: 99%
“…If lactoferrin itself acts as a transcriptional factor that binds to the promoter region of the specific gene, it must first be established that lactoferrin can be transported to the nucleus from the outside of the cell. Several researchers have reported on the lactoferrin-specific receptor to which lactoferrin binds, as well as the translocation of the intact lactoferrin into nucleus [Garre et al, 1992;Hu et al, 1990;Roiron et al, 1989;Mazurier et al, 1989]. Once it can be translocated into the nucleus, it binds easily to the DNA [Ravazzollo et al, 1988].…”
Section: Discussionmentioning
confidence: 99%
“…Lf has been evidenced in all epithelial cells at the luminal surface as an autochthonous product of the enterocytes [26], and the presence of Lf receptors has been demonstrated on the enteric mucosa of several species [11,16,25].…”
Section: Introductionmentioning
confidence: 99%
“…This most likely occur due to the structural similarity of the two glycoproteins. [51][52][53] With regard to transferrin and iron, the transferrin family is known to be potent regulators of iron homeostasis, 54 and Tfrc 1 is the primary target of transferrin in the iron transport system. It has been reported that low iron concentrations can lead to upregulation of this protein, 55 which may explain why Tfrc was differentially regulated by the iron unsaturated and saturated forms.…”
mentioning
confidence: 99%